(untitled) (Al-Farooq Journal of Sciences, 2026)
This scientific article comes at a time when the Al-Jabal Al-Akhdar region is witnessing rapid environmental and climatic transformations, which necessitate a reconsideration of the prevailing agricultural patterns and a serious shift towards more sustainable development options. From this perspective, this work seeks to provide an analytical review and a forward-looking vision for the prospects of the ’green transition’ in the region, focusing on ’agricultural extension’ as an indispensable cognitive and practical tool for altering traditional production behaviors. The article stems from a pivotal core concept: that agricultural residues—which are currently treated as an environmental burden, a source of visual pollution, and a fire hazard—fundamentally represent a wasted economic wealth that can be recycled and converted into vital inputs that support soil fertility and reduce the carbon footprint. By reviewing the biological foundations of organic composting processes and analyzing similar Maghreb experiences, the article proposes an integrated strategy, ’Al-Jabal Al-Akhdar 2030’. This strategy encompasses extension digitalization, green cooperatives, and youth investment, thereby serving as an academic contribution to drawing a roadmap for the environmental and agricultural future of the region